A pilot study of peripheral blood BDCA-1 (CD1c) positive dendritic cells pulsed with NY-ESO-1 ISCOMATRIX™ adjuvant. (March 2017) - Davis, Ian D; Quirk, Juliet; Morris, Leone; Seddon, Lauren; Tai, Tsin Yee; Whitty, Genevieve; Cavicchiolo, Tina; Ebert, Lisa; Jackson, Heather; Browning, Judy; MacGregor, Duncan; Wittke, Frederick; et al.
Aim: Pilot clinical trial of NY-ESO-1 (ESO) protein in ISCOMATRIX™ adjuvant pulsed onto peripheral blood dendritic cells (PBDC), to ascertain feasibility, evaluate toxicity and assess induction of ESO-specific immune responses.Patients & methods: Eligible participants had resected cancers expressing ESO or LAGE-1 and were at high risk of relapse. PBDC were produced using CliniMACS ® plus, with initial depletion of CD1c + B cells followed by positive selection of CD1c + PBDC. Patients received three intradermal vaccinations of ESO/IMX-pulsed PBDC at 4-week intervals.Results: The process was feasible and safe. No vaccine-induced immune responses were detected. Assays of immunomodulatory cells did not correlate with outcomes. One patient had a long lasting complete remission.Conclusion: This method was feasible and safe but was minimally immunogenic.